ANALISA PENGARUH PANDEMI COVID 19 TERHADAP TINGKAT PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI LHOKSEUKON KABUPATEN ACEH UTARA - Muzahid, Mukhlisul; Yazid AR, M. (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: The Covid-19 pandemic has caused a very significant decline in the turnover of Micro, Small and Medium Enterprises (MSMEs). This study aims to and analyze how much influence the Covid-19 pandemic has on the income of Micro, Small and Medium Enterprises (MSMEs) in Lhokseukon, North Aceh Regency. The research method used is descriptive quantitative method, using primary data sources through questionnaires and secondary from references to previous research results and online news that are directly related this research.This research stage starts from a preliminary survey to the market area and interviews with business actors to obtain information about the business and income level of MSMEs. In this study using the Linear Regression Analysis method with the consideration that the pattern of relationships between variables in the study is correlative and causal. This model will be able to answer the form of research problems so that the goal can be achieved, namely measuring how much influence the Covid 19 pandemic has on MSME business income. Respondents in this study were MSME business actors totaling 85 respondents with a purposive sampling approach. The results show that simultaneously and partially independent variables have a significant effect on the dependent variable.Keywords: Income, UMKM, Covid-19, Pandemic.